REPRESENTASI PESAN DAKWAH DALAM PERSPEKTIF KOMUNIKASI ISLAM PADA FILM “BILA ESOK IBU TIADA” MENURUT CLIFFORT GEERTZ DAN GEORGE HERBERT (TEORI INTERAKSIONISME SIMBOLIK) - Usman Usman; Firdaus El Hadi; Sartika Sartika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Films are very popular among the public today, the function of films as entertainment but without realizing it has a meaningful message contained in the content of the film's story. This study examines the film